تأثير استخدام نموذج التدريس Make a Match على استيعاب المفردات (بحث تجريبي في الصف الرابع بمدرسة عثمان بن عفان الإبتدائية الإسلامية مارندال سومطرة الشمالية) - Eliana, Khairida; Zaky, Ahmad; Aziz Shidiq, Abdul (Cahaya Ilmu Bangsa Institute, 2025)
The formulation of the problem in this research is whether there is an influence of using the Make a match learning model on the ability to master vocabulary in class IV of the Utsman bin Affan Marindal Islamic Elementary School, North Sumatra? This research aims to determine the effect of using the Make a match learning model on the ability to master vocabulary in class IV of the Utsman bin Affan Marindal Islamic Elementary School, North Sumatra. The research method used is true experimental design in the form of a posttest-only control design and the data analysis method used is statistics and the use of the SPSS 16 application. The results obtained from this research are that the average score of students who use the learning model is 68. 25 and the average score of students who did not use the learning model was 55.75. And finally, the researcher emphasized that the Make a match learning model has a big influence on students' ability to master mufradat because it can make it easier for them to master mufradat.